Effects of replacing timothy silage by alsike clover silage on performance, carcass traits and meat quality of finishing Aberdeen Angus and Nordic Red bulls. (12th August 2016) - Huuskonen, A.; Pesonen, M.; Honkavaara, M.
Abstract: The objective of the study was to determine the effects of silage plant species and cattle breed on performance and meat quality of finishing bulls. A feeding experiment was conducted using thirty Aberdeen Angus (AA) and thirty Nordic Red (NR) bulls. Both breeds were randomly allotted to three experimental diets. The composition (g kg −1 dry matter) of the diets was as follows: (i) timothy silage (TS) (650) and barley (350); (ii) TS (325), alsike clover silage (AS) (325) and barley (350); and (iii) AS (650) and barley (350). The bulls were fed a total mixed ration ad libitum . Replacing TS by AS did not affect dry‐matter intake, growth, carcass conformation or meat quality traits of the bulls, but carcass fat score tended to decrease when replacing TS by AS ( P  = 0·07). The AA bulls grew faster and had better feed conversion and superior carcass conformation compared with the NR bulls ( P  < 0·001). The loin of the AA bulls had lower shear force value and was given higher scores in sensory analyses compared with the NR bulls ( P  < 0·01). The experiment demonstrated that replacing TS by AS in the diet of finishing bulls had minor effects on performance or meat quality.